The complete chloroplast genome of Callicarpa integerrima var. chinensis (Lamiaceae) from Guilin, China, a potential medicinal plant. Issue 9 (2nd September 2021) - Gu, Chunjiao; Zhang, Qiang; Zhang, Deng; Zhang, Yancheng; Liang, Junsong
Abstract: Callicarpa integerrima var. chinensis is one of the traditional medical herbs which has the potential for multiple diseases' treatment. In this study, the complete chloroplast genome sequence of C. integerrima var. chinensis was sequenced and assembled. A typical quadripartite structure was observed in the chloroplast genome of C. integerrima var. chinensis which was 154179 bp in length, including a pair of inverted repeat (IR) regions (each 51396 bp) separated by a large single-copy region (LSC) of 84927 bp and a small single-copy region (SSC) of 17856 bp, and the overall GC contents of the chloroplast genome was 38.08%. Additionally, we annotated 132 genes, including 86 protein-coding genes, 38 tRNA genes, and 8 rRNA genes. Phylogenetic analysis was adopted which confirmed the position of C. integerrima var. chinensis was close to the congeneric C. formosana and C. siongsaiensis.